2021
DOI: 10.1038/s41598-020-80351-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of circulating cytokines VEGF, TNF-β and IL-15 indicate PD-L1 overexpression in tumours of primary breast cancer patients

Abstract: Programmed death ligand 1 (PD-L1) overexpression has been associated with poor clinical outcomes in several human cancers whose increased malignant behaviour might be related to PD-L1 mediated systemic immunological tolerance. This study aims to verify if circulating cytokines may serve as a proxy for non-invasive identification of sensitive prognostic biomarkers reflecting tumour and its microenvironment. Immunohistochemistry was used to measure PD-L1 expression in tumour tissue sections of 148 chemonaïve bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Currently, rare studies have checked the IL-15 expression in pan-cancer using tissue microassays except in those databases. Cierna et al (2021) found that decreased levels of circulating IL-15 suggested PD-L1 overexpression in tumors of primary breast cancer patients and poor prognosis. Krizia et al ( Cierna et al, 2021 ) reported that higher IL-15 levels would lead to better outcomes in prostate cancer, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Currently, rare studies have checked the IL-15 expression in pan-cancer using tissue microassays except in those databases. Cierna et al (2021) found that decreased levels of circulating IL-15 suggested PD-L1 overexpression in tumors of primary breast cancer patients and poor prognosis. Krizia et al ( Cierna et al, 2021 ) reported that higher IL-15 levels would lead to better outcomes in prostate cancer, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 98%
“… Cierna et al (2021) found that decreased levels of circulating IL-15 suggested PD-L1 overexpression in tumors of primary breast cancer patients and poor prognosis. Krizia et al ( Cierna et al, 2021 ) reported that higher IL-15 levels would lead to better outcomes in prostate cancer, which is consistent with our findings. Margolin et al (2018) recently found that the injection of IL-15N72D: IL-15RαSu/IgG1 Fc complex could reduce cancer growth, induce NK cell expansion and improve survival in patients with incurable advanced melanoma, renal cell, non-small cell lung, and head and neck cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 36 It has been recently shown that VEGF signalling exerts immune suppressive effects in BC tumours. 37 In hypoxia, the eukaryotic initiation factor 4E type 2 (EIF4E2 ) embarks on the translation of HIF‐2α‐bound mRNAs that contain hypoxia response elements. 38 Silencing of EIF4E2 in MDA‐MB‐231 triple‐negative cell line indicated a remarkable decrease in tumour cell migration and invasion during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The expression by cancer cells of programmed death ligand 1 (PD-L1), also known as CD274, plays a crucial role in the suppression of the immune system response; thus, it has been considered a therapeutic target in BC when overexpression is identified. However, PD-L1 is still under investigation due to the variability in expression and results as shown in different studies ( 98 ).…”
Section: Therapeutic Targets and Personalized Medicinementioning
confidence: 99%